THE SECOND HALF OF THE READYMADE CENTURY (1964–) - Daniels, Dieter (The Nordic Journal of Aesthetics, 2019)
The readymades conceived and selected by Marcel Duchamp be- tween the years 1914–1917 have, with very few exceptions, not survived until the present day as ‘original.’ A variety of forms, in- cluding documentary photos, objects chosen and approved later by Duchamp as well as remakes of the historical objects comprise the readymades’ legacy. Duchamp’s remakes of his readymades as a limited edition of multiples from 1964, commemorating the 50-year anniversary of his selection of the Bottle Dryer in 1914, mark the beginning of the second half of the “Readymade Century.” In contrast to their widespread visibility, the paradoxical ‘construct- edness’ of these objects is rarely discussed. The representational impact and the conceptual specificity of these multiples goes far beyond the oeuvre of Marcel Duchamp, and can be seen as a pre- monition of artistical appropriation strategies from the 1980s to the present day.